E-Commerce Coffepedia with Technology Acceptance Model (TAM) Testing - Alwin Laulio; Benny Daniawan; Suwitno Suwitno; Andri Wijaya (Komunitas Dosen Indonesia, 2022)
Coffee is one of the plantation commodities that has an important role in economic activities in Indonesia. Coffee is also one of Indonesia's export commodities which is quite important as a foreign exchange earner in addition to oil and gas. As a producer, Indonesia occupies the fourth position while as a consumer Indonesia is in seventh place, and coffee connoisseurs in Indonesia are growing rapidly at 8% for the development of coffee connoisseurs in Indonesia while the development of coffee connoisseurs in the world is only 6%. With the increase in coffee drinkers in Indonesia, the level of sales of coffee powder will also increase. In this study, the system was designed to facilitate the sale of coffee powder using prototyping methodology and the Technology Acceptance Model (TAM) for testing method. The purchasing system can make it easier and provide convenience for buyers and sellers in Indonesia. Based on the TAM test that has been carried out on 79 respondents, it shows the results that Attention to Use (ATU) affects Behavioral Intention to Use (BITU) by 4.427, Behavioral Intention to Use (BITU) affects Actual System Usage (ASU) 16.511, Perceived Ease of Use (PEOU) affects Attention to Use (ATU) by 3.130, Perceived Usefulness (PU) affects Attention to Use (ATU) by 6.712, and PU affects BITU by 4.692.